2018
DOI: 10.1038/s41375-018-0307-6
|View full text |Cite|
|
Sign up to set email alerts
|

Minimal residual disease quantification by flow cytometry provides reliable risk stratification in T-cell acute lymphoblastic leukemia

Abstract: Since the publication of the original paper, the authors realized in the analyses of day 15 MRD <25% and day 29 MRD data and outcome, three patients were misclassified due to non-censoring of event after HSCT. All three were stratified concordantly by FCM and PCR, two above (one relapse and one non-relapse related death) and one (relapse) below the cutoff level of 10 −3 . There is no change in the conclusions of the paper. An additional seven were misclassified but had day 15 MRD levels >0.25 and thus did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 30 publications
12
46
2
Order By: Relevance
“…A subset of children had bone marrow samples analyzed for MRD concurrently with chimerism analysis in peripheral blood. MRD was analyzed by RQ‐PCR according to the EuroMRD guidelines or by multicolor flow cytometry as described in the NOPHO ALL2008 guidelines . MRD results were categorized as either negative or positive < 10 −4 ; positive ≥ 10 −4 but <10 −3 ; positive ≥ 10 −3 ; or positive but below a quantitative range of 10 −3 …”
Section: Methodsmentioning
confidence: 99%
“…A subset of children had bone marrow samples analyzed for MRD concurrently with chimerism analysis in peripheral blood. MRD was analyzed by RQ‐PCR according to the EuroMRD guidelines or by multicolor flow cytometry as described in the NOPHO ALL2008 guidelines . MRD results were categorized as either negative or positive < 10 −4 ; positive ≥ 10 −4 but <10 −3 ; positive ≥ 10 −3 ; or positive but below a quantitative range of 10 −3 …”
Section: Methodsmentioning
confidence: 99%
“…MRD monitoring has redefined the concept of remission in pediatric ALL providing a reliable measurement of the drug sensitivity of leukemic lymphoblasts guiding better risk-directed therapy. Several studies have demonstrated a strong association between MRD levels and treatment outcome in childhood ALL (1,2,4). Accordingly, MRD techniques are currently utilized during and after induction therapy and for post remission monitoring to assess the response to therapy and to provide important information on the depth of post induction remission in essentially all major pediatric ALL protocols (6).…”
Section: Discussionmentioning
confidence: 99%
“…PCR-MRD monitoring was performed in parallel from day 29 according to the pre-T phenotype and protocol. Cytogenetic analysis revealed a clone with t(5;14) as the only aberration (46,XY,t(5;14)(q15; q32) [13]/46,XY [2]) confirmed by FISH to not involve TLX3. Multiplex PCR was negative for all 28 investigated translocations (8).…”
Section: Case IVmentioning
confidence: 94%
See 2 more Smart Citations